HUBUNGAN TINGKAT PENGETAHUAN IBU DENGAN TUMBUH KEMBANG BAYI PREMATUR USIA 6 SAMPAI 12 BULAN DI WILAYAH KERJA PUSKESMAS SE-KECAMATAN BANJARSARI - Saputra, Wahyu Indra; Irdawati, Irdawati (Universitas Muhammadiyah Surakarta, 2011)
Growth and development is something that remains to be seen not only in natural born infants but also in prematurely infants born. The levels of development with premature infants in the first year were generally lower than fullterm infants who were born on the same day. The results of a preliminary study of the information obtained from the midwife on duty at a district health center Banjarsari, during 2009-2010 have been 2 cases of mental retardation and one case of cerebral palsy. The research objective was to determine the relationship between the mother's level of knowledge to growth and development of preterm infants aged 6 to 12 months in the working area of a district health center Banjarsari. This research method using the correlation descriptive method with cross sectional approach. A sample size of 30 respondents using sampling techniques is the Total Sampling. Analysis of data using spearman rank techniques. Results showed that knowledge of mothers about growth and development of premature infants, shows most of the less (53%), the growth of premature infants largely normal (66.7%), the development of premature infants largely normal (66.7%), (4) The results of hypothesis test showed Ï= 0,393, p= 0,032 (p